Expression profile and bioinformatics analysis of circular RNA in intestinal mucosal injury and repair after severe burns. (30th September 2020) - Zhang, Wenwen; Yan, Hao; Deng, Yuequ; Lou, Jiaqi; Zhang, Pan; Cui, Qingwei; Sun, Han; Tang, Hao; Sun, Yuan; Yang, Juan; Li, Dan; Sun, Yong
Abstract: Circular RNA (circRNA) is a novel noncoding RNA that is mostly found in humans and animals. Although the flux of circRNA research has increased in recent years, its precise function is still unclear. Some studies demonstrate that circRNAs can function as microRNA (miRNA) sponges involved in the regulation of competitive endogenous RNAs networks and play a crucial role in many biological processes. Other studies show that circRNAs play multiple biological roles in gastrointestinal diseases. However, the expression characteristics and function of circRNA in intestinal mucosal injury and repair after severe burn have not been reported. This study aims to screen differentially expressed circRNAs in intestinal mucosal injury and repair after severe burns and understand their underlying mechanisms. To test our hypothesis that circRNA may play a role in promoting repair in intestinal mucosa injury after severe burns, we collected the intestinal tissues of three severely burned mice and three pseudo‐scalded mice and evaluated the expression of circRNAs via microarray analysis. Quantitative real‐time polymerase chain reaction was also used to validate the circRNA microarray data by selecting six based on different multiples, original values, and p  values. The host genes of all differentially expressed circRNAs and the downstream target genes of six selected DEcircRNAs were identified by Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes pathway analysis. Meanwhile, we also created a circRNA‐miRNA‐mRNA network to predict the role and function of circRNAs in intestinal mucosal injury and repair after severe burns.